z-9=-12

Simple and best practice solution for z-9=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-9=-12 equation:


z-9=-12

We simplify the equation to the form, which is simple to understand
z-9=-12

We move all terms containing z to the left and all other terms to the right.
+1z=-12+9

We simplify left and right side of the equation.
+1z=-3

We divide both sides of the equation by 1 to get z.
z=-3

See similar equations:

| y(x^2y^2-1)dx+x(x^2y^2+1)dy=0 | | 2tds+s(2+s^2t)dt=0 | | 2x+.33x=8 | | ax+by=y | | 15x+22x-7=x+3-10 | | (1+3x)(1-3x)=8x | | 5x+8y=365 | | 5y+9=7y+6-2y | | 5y-9=7y+6-2y | | 9+8x=8x+1 | | 189=7(3-6k) | | 176=8(1+7b) | | 2z+11=45 | | 6g=0 | | ab-cx=d | | 5(2x-2)-7x=5-(4x+3) | | 3x-3=31 | | 9(16w+81)=16 | | 6(8w+9)=8 | | 2p+9=21 | | 3(f-1)=9 | | 10(s-3)=-78 | | l-22/9=7/3 | | 7(3s+8)=308 | | 8x-14x+4x+1=59 | | 3x+4=5(x-5) | | -5x^2+15x-60=0 | | 3x-15=7x+12 | | 3+3y+5y=4-2y+3y | | (6y+2)+(2y+7)=12y-15 | | 9x-4=-1x-8 | | 3x+1=10-2x |

Equations solver categories